LEVERAGING THE ACTIVITY OF READING USING LINE WEBTOON: ITS EFFECT ON EFL STUDENTS’ VOCABULARY DEVELOPMENT - Winarti, Desita Ahadia; Kusuma, I Putu Indra (Lingua Scientia, 2024)
In technology era, the use of digital-based media is certainly a facility that has good prospects on the condition that it pays attention to techniques so that technology-based learning facilities are feasible to be integrated into English language teaching including in using digital comics as media in facilitating students in learning the language. The interest and enthusiasm of students to learn through the use of digital comics such as Webtoon make students feel confident in reading skills, this research was employed to determine the effect of using media digital comic Webtoon in teaching reading especially in sub skill vocabulary development. This research was a quasi-experimental research using a posttest-only control group design. This research used a quantitative approach. The research was conducted on SMP Negeri 4 Sawan, Grade IX students for the 2023/2024 academic year. The experimental group was taught using Webtoon, and the control group used conventional strategies. The sample was selected using an intact group sampling technique. The total population of this study was 129 students, and the sample was 64 students. Data was collected through a post-test through, a multiplechoice test given to students. Data were analyzed using the Mann Whitney U Test in the SPSS 26.0 program. The Mann-Whitney U test for independent samples shows a significant difference in students' vocabulary understanding between the experimental and control classes {Sig. (U) is smaller than 0.05}. The learning outcomes of the experimental class were higher than the control class (Mexp= 48.69; Mcon= 17.29). Based on these results, there was a significant influence on student's vocabulary development on teaching reading in grade IX students SMP Negeri 4 Sawan. Students' responses to the application of reading Webtoon in vocabulary development are positive. This can be seen from an increase in metacognition through increasing students' vocabulary development and in the affective aspect, namely increasing motivation, self-confidence, interest in learning, and students' sense of enjoyment. This research implied that a webtoon media was recommended for implementation by teachers in the classroom. Key Words: Teaching Reading, Vocabulary Development, Webtoon